Ion Pillat – de la vilegiaturist la rezident al Balcicului - Carmen Brăgaru (Revista de Istorie și Teorie Literară)
While in the first part of our study we closely followed Ion Pillat’s winding drawing near the small town-harbour on the southern coast of the Black Sea and his fascinating discovery of the dream[1]like space, in the second part, using various unknown so far documents found in the (Roumanian Academy Library) Archives, testimonies of the period and details taken from the poet’s correspondence, we try to reconstitute the different stages of Ion Pillat’s settlement in the town as a true citizen in the middle of the ’30s of the last century: his first buying of a land and the building of the first house (1933–1935), the purchasing of the second land, a bigger one this time (1934) and the building of the second smaller house (1936–1938). Once he delimitates his own domestic refuge, the poet tends to come to this inspiring solar and marine space as often as he can, though he never identifies with the artistic Bohemia, famous at that time, being rather a solitary taster of the landscapes. The chapter ends with Ion Pillat’s loss of his properties in Balchik on the background of Romania’s loss of the Cadrilater in the summer of 1940, as an epilogue describing the sad fate of his houses, so carefully and artistically conceived together with the Romanian architect Henrieta Delavrancea-Gibory.